Business Model Canvas : PortaPS / Mohamad Iqram Ab Nasir - Ab Nasir, Mohamad Iqram (2020)
Portaps, easier and instant power source no matter where you are. The value proposition of PortaPS is helping its customers in providing a backup power supply. Whenever they are about to use their laptop with the occurrence of no electricity, PortaPS can be used as an emergency power supply for charging the laptop or for using any low-watt consumed appliance such as the hair dryer. This can be very convenient to many of us. Unlike the power bank, PortaPS is developed with some technology enhancement which are temperature sensor and mobile-apps pairing. The value we are proposing is the better safety of usage to the customers. Concerning about the explosion that might take place when a lithium-ion- based product is left at a very high temperature place, these technologies seem to be useful and can increase the safety level of its user.